Diversidade de borboletas frugívoras em arquipélago de florestas tropicais montanas - Geanne Carla Novais Pereira (2016)
The roles of local and regional factors on structuring biological communities in the current scenario of land use change is of major importance due to increasing forest fragmentation. Although butterflies have been studied in oceanic islands and artificially fragmented forests, the processes driving these communities could be different from those driving communities in naturally fragmented landscapes. For the first time, we describe the effects of local vegetation structure and landscape in the community of frugivorous butterflies from an archipelago of montane rainforest islands in the Espinhaço Range in southeastern Brazil. Butterflies were collected with a bait trap in eleven forest islands through two consecutive collecting years, in both, dry and rainy seasons. The influence of local and landscape parameters, as well as the seasonality, on richness, abundance and butterfly species composition were analyzed. We further observed the partition of temporal and spatial beta diversity as well as the decomposition of beta diversity. 513 frugivorous butterflies belonging to 43 species were recorded in this study. The most abundant species was Godartiana muscosa (Satyrinae) with 188 individuals. The richness and abundance of fruit-feeding butterflies were higher on islands with greater canopy openness in the dry season. On the other hand, islands with lower understory coverage hosted higher richness and abundance of fruit-feeding butterflies in the rainy season. The landscape metrics, area and isolation, had no effect on richness and abundance of fruit-feeding butterflies. The composition of frugivorous butterflies from the forest islands were not randomly structured but instead were dependent of local and landscape effects, apart from the turnover mechanism as the main source of variation in its diversity. Thus, local habitat parameters were more important than the landscape ones in structuring the fruit-feeding butterfly community in the archipelago of montane forest. The preservation of the rainforest natural island complex is very important for the maintenance of fruit-feeding butterflies community, one island does not reflect the diversity found in the whole archipelago.